Analisis kasus tragedi Kanjuruhan menurut HAM dan Maqashid Syariah - Kamarudin, Faisal (Maliki Interdisciplinary Journal, 2024)
The incident that happened to the Arema superters was an unexpected incident. Which causes damage and losses suffered. Not only that, many victims fell because of the incident. So the writer is interested in discussing and revealing in his analysis through the perspective of HAM and Maqashid Syariah. Through actual reading sources in compiling and analyzing the case.